Struktur dan Fungsi Pasambahan Mampasandiangan Anak Daro jo Marapulai di Air Bangis Pasaman Barat - Juliastuti, Rafika; R., Syahrul; Amir, Amril (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this research is (1) describing the structure of pasambahan Mampasandiangan Anak Daro jo Marapulai at Kenagarian Air Bangis Kabupaten Pasaman Barat, (2) describing the function of pasambahan Mampasandiangan Anak Daro jo Marapulai at Kenagarian Air Bangis Kabupaten Pasaman Barat, (3)Â  The implication in Indonesia language study. The data of this research isÂ  pasambahan Mampasandiangan Anak Daro jo Marapulai. The sources of the data in this research getting from expression of pasambahan and successful interview with the informant. The collected of the data by write method and listening. Finding of the research is the structure of pasambahan consist of opening, to deliver of the meaning and closing. The plot of pasambahan consist of pasambahan manyiriah and pasambahan Mampasandiangan Anak Daro jo Marapulai. The function of pasambahan consist of social function, education function, moral function, tradition function, religious function and language function. The implication in Indonesia language study can give advantages on Indonesia language study at class X the second grade of Senior High School with the standard competition â€œto tell the information to pass write a paragraph and speech textâ€ and basic competence â€œto arrange of speech textâ€.